IMPLIKASI KEHADIRAN UNDANG-UNDANG HPP DAN INSENTIF PERPAJAKAN SEHUBUNGAN COVID 19 TERHADAP KEWAJIBAN PERPAJAKAN KLASTER PPN - Zara Tania Rahmadi; Muhammad Aria Wahyudi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
The global pandemic that has hit Indonesia since 2019 has weakened the Indonesian economy in all sectors including the state revenue sector through taxes, so the government needs to take extraordinary policies to restore the Indonesian economy, one of which is fiscal policy, namely the provision of taxes. incentives and also introduce regulations. new law related to tax policy. The existence of a tax harmonization law and tax incentive stimulus provided by the government facilitates tax obligations for taxpayers who can take advantage of it, especially in the VAT cluster. Based on the results of the study, it is known that the provision of value added tax incentives has a positive impact on increasing state revenues from the Value Added Tax (PPN) and Sales Tax on Luxury Goods (PPnBM) sectors of Rp. 38.43 trillion or grew 45.86 percent. When compared to 2020 in the same period, PPN and PPnBM contracted by 14.88 percent or Rp. 26.35 trillion. Thus, it can be concluded that the provision of incentives and the existence of the HPP Law in the VAT cluster provides convenience in tax obligations, thereby increasing state revenues and significantly restoring the Indonesian economy.